If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 7 = 1.2(10x + 12) Reorder the terms: 7 + 5x = 1.2(10x + 12) Reorder the terms: 7 + 5x = 1.2(12 + 10x) 7 + 5x = (12 * 1.2 + 10x * 1.2) 7 + 5x = (14.4 + 12x) Solving 7 + 5x = 14.4 + 12x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12x' to each side of the equation. 7 + 5x + -12x = 14.4 + 12x + -12x Combine like terms: 5x + -12x = -7x 7 + -7x = 14.4 + 12x + -12x Combine like terms: 12x + -12x = 0 7 + -7x = 14.4 + 0 7 + -7x = 14.4 Add '-7' to each side of the equation. 7 + -7 + -7x = 14.4 + -7 Combine like terms: 7 + -7 = 0 0 + -7x = 14.4 + -7 -7x = 14.4 + -7 Combine like terms: 14.4 + -7 = 7.4 -7x = 7.4 Divide each side by '-7'. x = -1.057142857 Simplifying x = -1.057142857
| 35(3-x)-20(2-3x)=150 | | 3=-3/5(m-9) | | 3+35x=15x+7 | | 2c-6=4c+4 | | x-(-8)=-32 | | 4v+2-2(-8v-1)=2(v-3) | | X(.75)=3 | | -2+2x=-3+7x | | 45=24(-7X) | | 45=24-7X | | 2=-z/8+13 | | 55-2x=10-7x | | 32-4x=8(-5x-5) | | 24-16x=-12x | | 5p-5=30 | | 2x-9-6x=-7x+5x | | 2x+5=-44-5x | | 6x+9=9x+6 | | =v^2+2v-8 | | -2p-36=-4(-6+8p) | | -4.2=-0.84(m+4) | | -8w+14=0 | | 7y=9x+6 | | x(x-3)=x^2+6x+8 | | 8x-(6x-3)=17 | | 84=-7+7(a+5) | | 1/3(b-3)=6 | | -4v-1=0 | | p^2q^2=36 | | -4*6+6y=-24 | | -5p+20=25 | | 3x^4*2w^4x^5*8w=x |